2018
DOI: 10.1111/tpj.13891
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic profiling reveals ABA‐responsive phosphosignaling pathways in Physcomitrella patens

Abstract: Abscisic acid (ABA) and its signaling system are important for land plants to survive in terrestrial conditions. Here, we took a phosphoproteomic approach to elucidate the ABA signaling network in Physcomitrella patens, a model species of basal land plants. Our phosphoproteomic analysis detected 4630 phosphopeptides from wild-type P. patens and two ABA-responsive mutants, a disruptant of group-A type-2C protein phosphatase (PP2C; ppabi1a/b) and AR7, a defective mutant in ARK, identified as an upstream regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…For detailed ABRE/ ABFs evolution see Cuming (2019). In addition, PpSnRK2s from P. patens and Arabidopsis SnRK2.6/OST1 phosphorylated in vitro the same ABA-responsive phosphopeptides (Amagai et al, 2018). Thus, not only is the kinase itself highly conserved, but also the cellular targets of class III SnRK2 are highly conserved, both from algae through angiosperms.…”
Section: The Pp2c-snrk2 Signaling Module Throughout Plant Evolutionmentioning
confidence: 99%
“…For detailed ABRE/ ABFs evolution see Cuming (2019). In addition, PpSnRK2s from P. patens and Arabidopsis SnRK2.6/OST1 phosphorylated in vitro the same ABA-responsive phosphopeptides (Amagai et al, 2018). Thus, not only is the kinase itself highly conserved, but also the cellular targets of class III SnRK2 are highly conserved, both from algae through angiosperms.…”
Section: The Pp2c-snrk2 Signaling Module Throughout Plant Evolutionmentioning
confidence: 99%
“…Protein phosphorylation is a universal PTM; however, the abundance of phosphorylation largely varies among different species. In C. moschata, the abundance of phosphorylated protein (2,853 phosphorylated proteins) was higher than most of the published species, such as Sus domesticus (966 phosphorylated proteins), Bombyx mori (2,112 phosphorylated proteins), Kandelia candel (1,516 phosphorylated proteins), Nicotiana tabacum (1,311 phosphorylated proteins), Lotus japonicus (1,154 phosphorylated proteins), Ammopiptanthus mongolicus (2,019 phosphorylated proteins), Catalpa fargesii (1,646 phosphorylated proteins), Abelmoschus esculentus (2,550 phosphorylated proteins), and Physcomitrella patens (1,873 phosphorylated proteins) 35,43,45,[50][51][52][53] . High-throughput method gives us an opportunity to screen potential phosphorylated proteins and reveal the involvement of protein phosphorylation in the responses to the C/NDRV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, SnRK2.2 and SnRK2.3 were not active in yeast and possibly require the additional expression of an upstream‐acting protein kinase in yeast. Candidates for such an activator might be the protein kinases BIN2 (Cai et al , ) and a mitogen‐activated protein kinase kinase kinase shown to activate SnRK2s under hyperosmotic stress in the moss Physcomitrella patens (Saruhashi et al , ; Amagai et al , ). Besides OST1, the subgroup I members SnRK2.1, SnRK2.4, SnRK2.5, and SnRK2.10 stimulated ABA signaling in our analysis.…”
Section: Discussionmentioning
confidence: 99%